Speech-language-hearing instruments to assess peripheral facial palsy: an integrative literature review - Pereira, Mariane (2021)
Purpose: to describe and analyze the clinical instruments that assess peripheral facial palsy through an integrative literature review. Methods: the precepts for this type of review were followed: research question, identification, selection of studies, and critical analysis. The Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), Google Scholar, and PubMed databases were accessed to search for fully available articles published in national journals between January 2008 and July 2018. The terms used in the search were “Speech, Language and Hearing Sciences”, “Evaluation”, and “Facial Paralysis”, in both English and Portuguese. The data obtained were organized per author, title, objective, instruments used, description of the instruments, and application procedures used in the articles. Results: out of the total 992 articles found, only 18 met the inclusion criteria of the research. In most of them, there was only the citation of the assessment instruments or considerations about them, without fully describing the application procedures. Conclusion: the study identified publications that indicate the use of clinical and speech-language-hearing assessment instruments. However, further detailing is necessary regarding the assessment procedures to help develop and refine the speech-language-hearing methodologies and techniques.